PEMANFAATAN E-KOMIK BERBASIS INKUIRI DALAM PEMBELAJARAN IPAS UNTUK MENINGKATKAN PEMAHAMAN KONSEP KEGIATAN EKONOMI SISWA SEKOLAH DASAR - Tati Alifah Ratnamaya; Sariakin; Siti Mayang Sari; Syarfuni (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to describe the utilization of inquiry-based e-comic media in IPAS (Integrated Science and Social Studies) learning and its impact on elementary students’ understanding of economic activity concepts. This research employed a qualitative approach with a descriptive method. The participants were fifth-grade students of SD Negeri 54 Banda Aceh. Data were collected through observation, interviews, and documentation. The results indicate that the use of inquiry-based e-comics enhances student engagement in the learning process, facilitates the understanding of abstract concepts, and encourages critical thinking through questioning and discovery activities. In addition, the implementation of e-comics creates a more interactive and enjoyable learning environment. In conclusion, inquiry-based e-comics can serve as an effective alternative learning media in IPAS instruction at the elementary school level.